SYMPTOMS OF INFANTS TOOTH GERMINATION: CONDITION OR DISEASE? - E. I. Kleschenko; I. A. Zhdanova; A. N. Lukisha; I. V. Krakovets; E. V. Smychkova; A. V. Kartavtseva (Кубанский научный медицинский вестник, 2017)
Aim. The purpose of this study was for identify the main orerall symptoms. Typilal for teething of children first year of life, including prematures, because uncontrolled using of medicines car lead of to advers and negative reactions.Materials and methods. The results of random survey of it children from 1 month to 1 year. 42 boys (55,3 %) and girls (44,7%) full-term Group included 40 children (63%), 36 children (47%) were included in preterm infants group.Results. The appearance of the first teeth is move common in 6-8 months оf babies life, painful teething was noted in 30 children (39,5 %). The most often symptoms were irritability, drooling, desire to bite. For relief of symptoms of 64 children, there was using medical funds. Of them prevailed gels (92,1% ).Conclusion. There is no specific symptoms of teething. To relive symptoms it is advisable to use safe medicines, pretembly of plant origin.